1 Answer | Add Yours
The integral `int dx/(5 - 3x)` has to be determined.
This can be done using substitution.
Let `y= 5 - 3x`
Differentiating both the sides with respect to x gives:
`dy/dx = -3`
`=> dx = -(dy)/3`
Substituting for 5 - 3x and dx in the original integral gives:
`int dx/(5 - 3x)`
= `-(1/3) int dy/y`
= `-(1/3)*ln y`
As y = 5 - 3x, the integral is:
`-(1/3)*ln (5 - 3x)`
The integral `int dx/(5 - 3x) = -(1/3)*ln (5 - 3x)`
We’ve answered 319,627 questions. We can answer yours, too.Ask a question